Iron Oxide Nanoparticles Synthesis From Vermicomposting Leachate and its Antioxidant Activities - Arslan, Hudaverdi; Gonca, Serpil; Isik, Zelal; Özdemir, Sadin; Yalvac, Mutlu; Dizge, Nadir; Deepanraj, Balakrishnan; Ashraf, Ghulam Abbas (Frontiers in Materials, 2022)
Currently, nanotechnology and nanoparticles have been quickly emerged and have gained the attention of scientists due to their massive applications in environmental sectors. Nanotechnology also encompasses the ability to design, characterize, manufacture, and implement nano-sized structures. Today, metal oxide nanoparticles stand out in industrial applications in various fields of applied nanotechnology. Among metal oxide nanoparticles, iron oxide nanoparticles (FeO-NPs) are one of the widely used NPs. Green chemistry-based nanoparticles production is one of the most interesting topics in recent years. In the present study, we used vermicomposting leachate to synthesize FeO-NPs. First, vermicomposting leachate (VCL) was produced and then FeO-NPs was obtained from ferric chloride salt. FeO-NPs was characterized by scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM/EDX) and X-ray diffraction (XRD). Additionally, the antioxidant activities of FeO-NPs synthesized from vermicomposting leachate (VCL-FeO-NPs) were evaluated by DPPH scavenging activity. The highest DPPH activities of VCL-FeO-NPs at 200 mg/L concentration were 93.54%. In addition, the nanoparticles showed significant DNA nuclease activity. The antimicrobial activities of VCL-FeO-NPs were studied in micro dilution methods and it exhibited moderate antimicrobial activity through Gr +ve, Gr –ve, and fungi. The nanoparticles showed more effective microbial cell inhibition activity against E. coli. Also, biofilm inhibition results were detected against S. aureus and P. aeruginosa were 66.05% and 67.29%, respectively.